1995
DOI: 10.1093/ptj/75.7.621
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transcutaneous Electrical Nerve Stimulation on Skin Temperature in Asymptomatic Subjects

Abstract: High-intensity, low-frequency TENS prevented cooling of the hand. High- and low-frequency TENS had no effect on finger temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
15

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 21 publications
1
33
0
15
Order By: Relevance
“…Transcutaneous electrical nerve stimulation (TENS) is a well defined method of pain management; however, some studies found an increase in skin temperature and perfusion in healthy subjects (21). This important discovery prompted research into the effects of TENS on chronic ulcers and flaps.…”
Section: Abstract: Electrical Stimulation; Flaps; Rats; Viabilitymentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation (TENS) is a well defined method of pain management; however, some studies found an increase in skin temperature and perfusion in healthy subjects (21). This important discovery prompted research into the effects of TENS on chronic ulcers and flaps.…”
Section: Abstract: Electrical Stimulation; Flaps; Rats; Viabilitymentioning
confidence: 99%
“…2,18 The TENS is a well-known, low cost and easy-to-use therapeutic source to control acute and chronic pain. 32 Besides the analgesic effect, some researches demonstrated that TENS application alters the temperature and cutaneous blood flow 19,20,23,33,34 enlarging the range of indications for the use of TENS in the treatment of chronic ulcers 22,25,35,36 and ischemic skin flaps. 6,7,18 The present study showed that TENS treatments may increase the viability of skin flap in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29] Based on these findings, the present study was therefore designed to evaluate the effect of low-frequency TENS at different pulse amplitudes on the viability of ischemic skin flap in the rat.…”
mentioning
confidence: 99%
“…Several investigators have noted greater increases in skin temperature following low-frequency rather than highfrequency TENS~Abram, Asiddao, & Reynolds, 1980;Kaada, 1982;Scudds, Helewa, & Scudds, 1995!. The failure of some previous research to detect changes in autonomic function following lowfrequency stimulation is likely the result of variability in electrode location, intensity, and duration.…”
mentioning
confidence: 99%